Record of an alleged Solitary Eagle in Oaxaca is a Great Black Hawk - Clark, William S.; Clinton-Eitniear, Jack; Phillips, Ryan A. (Instituto de Ecología, A.C., 2020)
In a recent article in this journal (García-Grajales et al., 2018), an adult Great Black Hawk (Buteogallus urubitinga) was mistakenly identified as an adult of the Solitary Eagle (Buteogallus solitarius). The Solitary Eagle differs from the Greater Black Eagle in having the longest and widest wings, and the shortest tail. These characteristics give it a more triangular shape in flight. These differences are easy to see in Figures 1–3. The same authors also cite a case of the nesting of the Solitary Eagle in Mexico (Smith, 1982). However, after reviewing photos of the young, we consider that this record is probably the Common Black Hawk (B. anthracinus). The illustrations of the Solitary Eagle in field guides of Mexico and Central America (Howell & Webb, 1995; Van Perlo, 2006) demonstrate greater similarity with the Great Black Hawk, contributing to the frequent confusion of the two species if used without consulting the text. The new features published here and in Clark et al. (2006) and Clark and Schmitt (2017) should help with correct identification of Buteogallus species in the future.